The Iranian Nuclear Project: Developments and Environmental Implications for the Middle East (1957–2010) - Nouidji, Sana; Hemamid, Hassina; Zitoune, Kaima (Journal of Ecohumanism, 2025)
The Iranian nuclear project represents a central issue in the international system. Its political and security dimensions intersect with economic, strategic, and environmental concerns. While global discussions often focus on security and nuclear proliferation, the environmental dimension is no less critical. It carries the potential for catastrophic consequences affecting Iran, neighboring countries, and possibly the world. Among the most serious risks are direct environmental threats linked to nuclear reactors and the transboundary regional effects they could cause. This paper highlights the importance of integrating environmental concerns into both regional and international policy-making. Neglecting this aspect of Iran’s nuclear file may not threaten a single state alone but poses a danger to the entire Middle East. Since the main aim of this article is to examine the environmental risks arising from Iran’s nuclear facilities, it is essential to understand the components of the nuclear program and the key areas of international contention surrounding it. Although originally intended for peaceful purposes such as electricity generation, medical isotopes, and scientific research its strategic implications have raised widespread concerns.